الثقافة التنظيمية وتأثيرها على تطبيق الإدارة الإلكترونية من وجهة نظر موظفي صندوق الضمان الاجتماعي في فرع شرق بنغازي - مفتاح محمد المصراتي, سالمة (Dirasat in Economics and Business, 2026)
The study aimed to reveal the impact of organizational culture on the application of e-management from the point of view of employees in the Social Security Fund in the East Benghazi branch. The study followed the case study methodology and used a questionnaire as the primary tool for collecting data. The research community consisted of all employees in the mentioned branch, numbering 110 employees. The data were analyzed and hypotheses were tested using SPSS. The study reached several main results, including: a high level of organizational culture and the degree of application of e-management, and the existence of a statistical impact of organizational culture on e-management. The study proposed several recommendations, including: enhancing and disseminating the concepts of organizational culture and e-management among employees in Libyan institutions, updating and developing systems and laws to meet the needs of employees, and developing training plans to support e-transformation and train employees on program and service updates.